Modern weapons and military equipment for issue 1-2018 - Jevtić, Miloš M. (Vojnotehnički glasnik / Military Technical Courier, 2017)
Equipment for the emergency response of the Serbian Armed Forces. Configuration of equipment for the needs of special operations.